Digital horizons: understanding teacher retention challenges in Myanmar's rural basic education schools through the lens of informatization - Wynn Marlar; Mohamad Zreik (RUDN Journal of Informatization in Education)
Problem statement. The study delves into the multifaceted challenges of teacher retention in rural public basic education schools in Myanmar, with a special focus on the role of informatization in education. In areas often marginalized and facing unique socio-economic constraints, teacher turnover has become a pressing issue, impacting the quality of education. Methodology. This research adopts a qualitative insight from educators, to dissect the core factors influencing teacher retention. Key findings highlight inadequate infrastructural facilities, limited professional development opportunities, and socio-cultural barriers as primary deterrents. Results. The study uncovers how informatization - the integration of information and communication technologies (ICT) in education - can mitigate these challenges. It emphasizes that informatization not only enhances teaching-learning processes but also serves as a catalyst for teacher motivation and job satisfaction. Conclusion. The paper concludes with recommendations for policy interventions, emphasizing the need for a harmonized approach that interlaces traditional educational strategies with modern ICT solutions to foster a more stable and effective teaching workforce in Myanmar's rural landscapes.